Taming the Tongue: The Surgical Approach to Macroglossia. Issue 1 (3rd January 2023) - Lerner, Julia L.; Borrelli, Mimi R.; Jehle, Charles C.; Benz, Elizabeth G.; Brown, Steven A.
Abstract : While traditionally in the realm of otorhinolaryngology or oral maxillofacial surgery, conditions involving the tongue may also be managed by plastic surgeons. The authors present an unusual case of acquired macroglossia resulting from angiotensin-converting enzyme inhibitor–induced angioedema and review the literature to discuss its surgical management from a plastic surgery perspective. A 62-year-old female suffered severe airway obstruction, respiratory arrest, and anoxic brain injury from angioedema-associated macroglossia. After tracheostomy, the patient was managed nonsurgically, with bite wound care and medications to minimize angioedema to marginal effect. Ultimately, a partial glossectomy was planned. The edematous distal tongue was amputated and closed primarily. On postoperative day 2, she was successfully weaned off mechanical ventilation and no longer suffers trauma from tongue biting. The simple anterior tongue resection described in this paper was an appropriate approach for our patient. More research is needed to guide plastic surgeons in an optimal approach for clinical scenarios.